Intergenerational Mobility Between and Within Canada and the United States - Connolly, Marie; Corak, Miles; Haeck, Catherine (Journal of Labor Economics, 2019)
Intergenerational income mobility is lower in the United States than in Canada but varies significantly within each country. Our subnational analysis finds that the national border only partially distinguishes the approximately 1,000 regions we analyze within these countries. The Canada-US border divides central and eastern Canada from the US Great Lakes and northeastern regions. Simultaneously, some Canadian regions have more in common with the low-mobility southern parts of the United States than with the rest of Canada; that these areas represent a much larger fraction of the US population also explains why mobility is lower in the United States.